THE CONTRIBUTION OF STUDENTS TEAM ACHIEVEMENT DIVISION (STAD) AND MOTIVATION TOWARDS WRITING COMPARISON AND CONTRAST TEXT OF THE FIRST SEMESTER MANAGEMENT STUDENTS AT UNIVERSITY MUHAMMADIYAH OF METRO - Thresiaz, Fenny (JURNAL PEDAGOGY, 2013)
Abstract : The purpose of the present study is to explore the positive effects of Student Teams Achievement Division (STAD) on other important factors such as studentsâ motivation. STAD was used with thirty students and was compared to thirty management students who worked in groups lacking the key components of STAD. Both groups completed pretest and posttest and responded in motivational questionnaire which measured changes in exposure to writing skill in English. The findings showed that (1) there was a significant progress within each group, (2) there was also significant mean difference between the experimental and control group with the contribution of the STADÂ  approach to studentsâ motivation and to writing achievement.Â Keywords: Student Teams Achievement Division (STAD), motivation and writing skill